Field research forms for a study on nominative typography in Rio de Janeiro city architecture - Salomon, Carlos Alexandre Xavier; Gouveia, Anna Paula Silva; Farias, Priscila Lena (InfoDesign, 2025)
This article discusses the adaptation of the methodological procedures adopted by the research project ‘Typographic Landscapes’ (PAT), jointly developed by the research groups ‘Typography and Graphic Language’ (Centro Universitário Senac) and São Paulo City Architectural Typography (UNICAMP) for an investigation on Rio de Janeiro city architectural typography (TAC). The paper shows how the recording system developed for São Paulo city was modified and applied in the context of Rio de Janeiro city historical centre, endowing an information gathering more adequate to this specific urban environment.